Association of plant‐based diet and type 2 diabetes mellitus in Chinese rural adults: The Henan Rural Cohort Study. Issue 9 (2nd March 2021) - Yang, Xiu; Li, Yuqian; Wang, Chongjian; Mao, Zhenxing; Chen, Yu; Ren, Pengfei; Fan, Mengying; Cui, Songyang; Niu, Kailin; Gu, Ruohua; Li, Linlin
Abstract: Aims/Introduction: Studies have found that a plant‐based diet was associated with a lower risk of type 2 diabetes, but evidence is scarce on such associations in China. The aim of this study was to investigate whether a plant‐based diet is related to a lower risk of type 2 diabetes among Chinese adults. Materials and Methods: A total of 37, 985 participants were enrolled from the Henan Rural Cohort Study. An overall plant‐based diet index (PDI) was created by assigning positive and reverse scores to 12 commonly consumed food groups. Multivariate logistic regression models and restricted cubic spline analysis were performed to estimate the odds ratio (OR) and 95% confidence interval (95% CI). Results: After multivariable adjustment, the risk of type 2 diabetes was inversely associated with the PDI (extreme‐quartile OR = 0.88, 95% CI: 0.79–0.98; P = 0.027), the risk associated with a 1 standard deviation (SD) increase in PDI was 4% lower (95% CI, 0.93–1.00; P trend = 0.043) for type 2 diabetes. Moreover, the odds of type 2 diabetes was decreased with an increment of PDI after fitting restricted cubic splines ( P trend < 0.01). Conclusions: Among Chinese populations, diets higher in plant foods and lower in animal foods were associated with a reduced risk of type 2 diabetes. Abstract : This is the first study to evaluate the association between the plant‐based diet index (PDI) and type 2 diabetes in a Chinese rural population. In our study, a higher PDI score was associated with a lower risk of type 2 diabetes, and a 1 standard deviation (SD) increase in PDI was associated with a 4% lower risk of type 2 diabetes.